On-farm Conservation Approaches for Agricultural Biodiversity in Nepal - Joshi, Bal Krishna; Upadhya, Deepak (Journal of Agriculture and Natural Resources, 2019)
Agricultural biodiversity is the basis for agricultural research and development. This paper is based on the survey across the country along with the field implementation and action research on different conservation approaches over the years and locations. Management of agricultural biodiversity is being initiated in Nepal through ex-situ, on-farm, in-situ and breeding strategies by National Agriculture Genetic Resources Center (National Genebank) from 2010. National Genebank has implemented on-farm conservation across the country. Different approaches are community seed bank, community field genebank, household seed bank, household field genebank, village level field genebank and school field genebank. In addition to these, landrace enhancement program and recognition of agro-biodiversity rich farmers have also contributed on conserving APGRs. Identification of agro-biodiversity rich farmers have been initiated in collaboration with different governmental and non-governmental organizations across the country. Strong network among these farmers is supposed to establish for effectively managing APGRs on-farm. Agro-biodiversity conserved by such farmers is called household genebank, which consist of seed storage (household seed bank) and household field genebank. There are more than 100 CSBs in the country and some of them are conserving local genetic resources. Eight community field genebanks have been functionalized for conserving recalcitrant seeds and vegetatively propagated crop species. Village level field genebank has been established by NGO in Makwanpur district to conserve banana and taro. In this approach, different households grow different landraces, maintaining maximum diversity within a village. In some areas, school field genebank has been established by growing local APGRs in school areas. This helps to conserve APGRs, educate the students, earn the income and make environment beautiful. Genebank also encourages farmers to reintroduce the landraces from the National Genebank. Accessioning these APGRs and training to farmers and farming communities are necessary to effectively and efficiently conserving and utilizing APGRs on-farm.